PENGARUH RASIO KEUANGAN TERHADAP PERINGKAT SUKUK - Malia, Lidiya; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The rate of sukuk can become the consideration for the investors to purchase the sukuk of a company since the rate of sukuk is an informative statement which can be used as the standards of the risk of investment failure. The rate of sukuk can be influenced by various factors and one of the factors is the financial factor of the company which is analyzed by using financial ratio. The purpose of this research is to test the influence of the financial ratio (liquidity, productivity, profitability, and solvability) to the rate of sukuk. The samples are 17 companies which have been selected by using purposive sampling of the companies which have published their sukuk which are listed in Indonesia Stock Exchange and Indonesia Bond Market Directory in 2009-2013 periods. The quantitative method have been used the method of research and the analysis technique has been done by using multiple linear regressions and SPSS statistic test instrument 16.0 version. The result of the research shows that liquidity ratio, productivity ratio, profitability ratio, and solvability ratio simultaneously have an influence to the rate of sukuk and it is feasible to be the research model. The result of partial test shows that liquidity ratio and solvability ratio has positive influence to the rate of sukuk whereas productivity ratio and profitability ratio does not have any influence to the rate of sukuk.Keywords: Sukuk, Liquidity, Productivity, Profitability, Solvability